Path Analysis on the Determinants of Pap Smear Uptake in Women of Reproductive Age in Tegal, Central Java (Journal of Maternal and Child Health, 2019)
Background: Cervical cancer is a leading cause of cancer-related deaths in women in developing countries. Although Pap smear is known as an effective strategy to reduce the burden of cervical cancer, it is underused in developing countries at around 19%. This study aimed to examine the determinants of Pap smear uptake in women of reproductive age using Health Belief Model (HBM).Subjects and Method: This was a case-control study conducted in Tegal, Central Java, from October 4 to November 2, 2018. A sample of 200 women of reproductive age was selected by fixed disease sampling. The dependent variable was Pap smear uptake. The independent variables were perceived benefit, susceptibility, seriousness, and threat, cues to action, education, knowledge, and peer support. The data were collected by questionnaire and analyzed by path analysis run on Stata 13.Results: Pap smear uptake directly increased with stronger perceived threat (b= 1.18; 95% CI= 0.44 to 1.92; p=0.002), stronger perceived benefit (b= 1.40; 95% CI= 0.63 to 2.16; p